Comparison of GA and topology optimization of adherend for adhesively bonded metal composite joints - Arhore, Edore G.; Yasaee, Mehdi; Dayyani, Iman (Elsevier, 2021)
This paper investigates the effect of the outer adherend geometry on the strength of an adhesively bonded joint. The investigation was carried out by optimizing the joint geometry using two different numerical optimization methods. In genetic algorithm (GA) optimization with high fidelity explicit finite element analysis (FEA) and topology optimization (TOP). Both procedures were utilized on a simplified pseudo-2D model as well as a full-scale 3D model. The results showed that the outer adherend geometry directly affects the strength of a joint subjected to tensile load. For joints subjected to bending load, the geometry had little to no effect on the strength of the joint. The GA optimization process produced identical geometry for both 2D and 3D models. However, the TOP process produced different optimum geometries. The optimum joints produced by the TOP process offered the highest strength overall, while the optimum GA joint produced the best strength to weight ratio. The reasons for these results and other features of the optimized designs, including interface stress, failure mechanisms and computational efficiency are discussed in detail.
Keywords: continuum damage model (CDM); cohesive zone modelling (CZM); MATLAB; topology optimization; genetic algorithm; optimization procedure; ANSYS; Abaqus; adhesive joints; CFRP composites; Adherend